2022
DOI: 10.1016/j.eats.2021.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Semitendinosus Allograft Cable Reconstruction Technique for Massive Irreparable Rotator Cuff Tears

Abstract: Massive irreparable rotator cuff tears are difficult to treat. Disruption of the rotator cable and joint capsule leads to altered glenohumeral joint mechanics, superior migration of the humeral head, and limited overhead function. A few graft options exist for reconstruction, with limited outcomes data. A newer technique using a hamstring allograft provides benefits compared with other graft reconstruction options. This Technical Note describes a rotator cable reconstruction using a V-shaped hamstring allograf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…Graft options for augmentation include fascia lata, 40 LHBT, 36 semitendinosus tendon, 9 and acellular dermal allografts. 15 The selection of the LHBT as an autograft source is convincing owing to its anatomy being similar to that of the anterior cable and the common pathology of rotator cuff tears, which are usually treated with tenotomy or tenodesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Graft options for augmentation include fascia lata, 40 LHBT, 36 semitendinosus tendon, 9 and acellular dermal allografts. 15 The selection of the LHBT as an autograft source is convincing owing to its anatomy being similar to that of the anterior cable and the common pathology of rotator cuff tears, which are usually treated with tenotomy or tenodesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that the semitendinosus tendon has several advantages as a graft option for ARCR reinforcement. 9 , 17 , 47 First, the semitendinosus tendon is a standard graft source due to the harvesting technique, sufficient length and strength, and minimal donor-site morbidity. Biomechanically, the hamstring has been described as a static stabilizer that allows sufficient centering of the humeral head.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 These tears directly affect normal biomechanics by disrupting active and passive restraints. 12 While several treatment options have been described for these tears, the failure rate remains unacceptably high. 11 , 13 , 14 Therefore, it is imperative for surgeons to improve treatment strategies for the treatment of MIRCTs to obtain better postoperative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Other joint-preserving procedures, including superior capsule reconstruction and cable reconstruction, have been proposed to treat MIRCTs. 12 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 However, our technique presents some advantages, including less surgical time, it is technically easier, and potential cost savings. A disadvantage is that as the rotator cuff is not repaired completely, our technique may not be preferable for young and active patients where the risk of progression is of greater concern.…”
Section: Discussionmentioning
confidence: 99%